Patterns of Urology Practice In A Small Rural Hospital of Developing Country - Bhamer Cal Lakhani, Muhammad Ali Suhail, Feroz Ali Ahmed, Gulshan Ali Memon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To delineate the urology experience in a small rural hospital. Study design: Descriptive, observational study. Place & Duration: Civil Hospital Mithi from July 2009-Jun 2012. Material and Methods: The operative experience between July 2009 to June 2012, at District head quarter hospital in rural Tharparker was evaluated. Data of all urological cases at DHQ Hospital Mithi was collected on a proforma regarding age, sex, residence, diagnosis. category of operations, range of procedures by single doctor and complications. In all patients’ basic laboratory tests like CBP, urine analysis, renal function was done, the X-ray & ultrasound studies were also done where ever necessary. Results: Urologic procedures performed in total 851 patients. All were belonging to rural Tharparker with low socioeconomic status. Of 851 patients 750(88.1%) were male. Among the 851 cases 221 (26%) were children and 630(74%) were adults. The mean age of patients was 39.4 (range 3months to 85 years). In pediatric groups of 221 patients. 202(91.4%) were male. The five most frequent procedures in 851 cases were difficult urethral catheterization 213(5% ). cystolilhotomies 153(18%), circumcision and glans refreshing due to Balanitis Xerotica Obliterance (BXO) 127 ( 14.9%) Inguinal Hernioraphy 78(9.1%) and suprapubic cystostomies 53(6.2%). Open procedures performed in 818(96.1%) patients and endoscopic procedures performed in 33(3.9%) patients. Most common complications were wound infection 38(4.5%). hematuria 18(2.1%), scrotal hematonias 6(0.7%). Conclusion: Patients in rural areas living with advanced and complicated urological diseases. Establishment of urological setup in rural hospitals is urgent need of developing country. Key Words: District hospital urology, Rural urology. Small setup urology,